2000
DOI: 10.1007/pl00007291
|View full text |Cite
|
Sign up to set email alerts
|

Secondary tethered cord syndrome in spinal dysraphism

Abstract: Secondary tethered cord syndrome following initial repair for spinal dysraphism is an important area of interest. In this study, 32 cases with spinal dysraphism in the lumbosacral region were enrolled, in whom radical repair with autologous material had been carried out in the early stage soon after birth. During the follow-up period of up to 19 years 10 months, surgery was considered to be indicated in 2 of the 8 lipomeningocele cases and in 6 of the 24 meningocele and meningomyelocele cases, because of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 22 publications
0
17
0
1
Order By: Relevance
“…Loss of neurological function has also been demonstrated to have a logarithmic association with increasing patient age and is believed to be secondary to increased stretch on the spinal cord with axial growth spurts. 26,27,33,52 Other theories regarding the mechanism of progression of symptoms include decreased perfusion secondary to stretch on the spinal cord, increased mass effect from progressive deposition of fat, and stretching effects on the spinal cord. 51,52,71 Hoffman et al 27 observed that 62.5% of patients were neurologically asymptomatic prior to 6 months of age, while only 29.3% were asymptomatic after 6 months of age.…”
Section: Diagnosis and Presentationmentioning
confidence: 99%
“…Loss of neurological function has also been demonstrated to have a logarithmic association with increasing patient age and is believed to be secondary to increased stretch on the spinal cord with axial growth spurts. 26,27,33,52 Other theories regarding the mechanism of progression of symptoms include decreased perfusion secondary to stretch on the spinal cord, increased mass effect from progressive deposition of fat, and stretching effects on the spinal cord. 51,52,71 Hoffman et al 27 observed that 62.5% of patients were neurologically asymptomatic prior to 6 months of age, while only 29.3% were asymptomatic after 6 months of age.…”
Section: Diagnosis and Presentationmentioning
confidence: 99%
“…Surgical series have shown retethering rates approaching 45% in more complex cases of myelomeningocele and lipomyelomeningocele; in cases of thick/fatty filum terminale sectioning, considerably lower rates have been reported, and scattered reports in the literature cite a retethering rate of about 8%-9% on long-term follow-up. 6,7,16 Most retethering is attributed to scar and arachnoid adherence around the neural elements attached to the spinal meninges, developing traction and nerve root dysfunction over time. 15 Maintenance of a pristine subarachnoid space during surgery and robust irrigation prior to dural closure have been espoused as technical nuances thought to minimize the risk of intradural adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, approximately 75-90% of patients experience improvement or stabilization of symptoms. 1,7,9,12,18 Pain is most amenable to improvement; AlHolou and col leagues 1 recently reported improvement in pain in 75% of patients. 9,10,12,20 Bowel and bladder function, on the other hand, are less likely to improve, with only 13-46% of patients reporting improved function (20% in this se ries).…”
Section: Posttreatment Outcomesmentioning
confidence: 99%
“…1,7,9,12,18 Pain is most amenable to improvement; AlHolou and col leagues 1 recently reported improvement in pain in 75% of patients. 9,10,12,20 Bowel and bladder function, on the other hand, are less likely to improve, with only 13-46% of patients reporting improved function (20% in this se ries). 1,7,17,22 In addition, we suspect that untethering contrib uted to the stabilization of bowel and bladder function in the other patients who presented with these symptoms.…”
Section: Posttreatment Outcomesmentioning
confidence: 99%
See 1 more Smart Citation